2022
DOI: 10.1177/10760296221107020
|View full text |Cite
|
Sign up to set email alerts
|

Using the Caprini Risk Score to Increase VTE Awareness in the Community: The Know Your Score Project

Abstract: presented during the ISTH congress 2021 Shetye, P., Gavankar, S, Saadaldin, H, et al, Using the Caprini Risk Score to Increase VTE Awareness in the Community. The Know Your Score Project. AS-ISTH-2021-02054, 2021

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These findings confirm and extend previous observations about VTE risk level and factors in the community. 7 Our results revealed that a total of 247 (26.6%) participants reported they had family blood clot history, and 130 (52.6%) participants were less than 40 years old. Family history is an important risk factor to predict VTE in those without a personal history of thrombosis having surgery.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These findings confirm and extend previous observations about VTE risk level and factors in the community. 7 Our results revealed that a total of 247 (26.6%) participants reported they had family blood clot history, and 130 (52.6%) participants were less than 40 years old. Family history is an important risk factor to predict VTE in those without a personal history of thrombosis having surgery.…”
Section: Discussionmentioning
confidence: 60%
“…Important variables collected ahead of time, including family history of thrombosis, can result in a better estimation of a patient's risk and be very valuable to the treating physician in managing the patient. Previous research has demonstrated the value of gathering this information prior to getting ill. 7 …”
Section: Introductionmentioning
confidence: 99%
“…[ 60 ] The Caprini Risk Score is a comprehensive list of 41 thrombosis risk factors validated in >5 million patients. [ 61 ] It is the most widely used and validated RAM for surgical patients. [ 40 , 41 , 43 ] A retrospective study on arthroplasty patients reported that Caprini RAM provides an effective, consistent, and accurate method of VTE risk stratification in these surgical patients.…”
Section: Rams According To Underlying Conditionmentioning
confidence: 99%